PELATIHAN DIVERSIFIKASI PANGAN LOKAL BERBAHAN DASAR JAGUNG UNTUK MENUNJANG PEMBELAJARAN PRAKARYA BAGI GURU SMA NEGERI 3 SERAM BARAT - Sinay, Hermalina; Gysberthus, Yolanda; Kakisina, Susan (Universitas Pattimura, 2022)
Corn is one of the local food sources that can be developed into various processed products. The purpose of this program was to provide information about the techniques for making local corn-based processed food products, and to determine the level of participants' satisfaction with the training activities including the benefits in supporting the craft learning of Senior High School 3 West Seram Regency. Activities were carried out in three stages, namely preparation, implementation, and evaluation. At the implementation stage, it was divided into two, namely counseling and training. At the evaluation stage, a questionnaire was given to measure the level of participants' satisfaction with the activities carried out. The results obtained showed that the participants were very enthusiastic in participating in the training activities from the preparation, implementation and evaluation. The results of measuring the level of satisfaction showed that participants were very satisfied with the activities carried out both from the competency aspect of the resource persons (90%), the material presented (87.5%), the results obtained (89.37%), and the benefits of the results to support craft learning. (91.45%). Thus, it can be concluded that the participants were enthusiastic about participating in the training on diversification of local food products made from corn. Participants received additional information and new skills that support craft learning, participants were very satisfied with the training activities carried out, and the training activities carried out were very supportive in learning crafts by teachers at Senior High School 3 West Seram Regency